2016
DOI: 10.1371/journal.pone.0169202
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fully Automated VMAT Plan Generation for Library-Based Plan-of-the-Day Cervical Cancer Radiotherapy

Abstract: PurposeTo develop and validate fully automated generation of VMAT plan-libraries for plan-of-the-day adaptive radiotherapy in locally-advanced cervical cancer.Material and MethodsOur framework for fully automated treatment plan generation (Erasmus-iCycle) was adapted to create dual-arc VMAT treatment plan libraries for cervical cancer patients. For each of 34 patients, automatically generated VMAT plans (autoVMAT) were compared to manually generated, clinically delivered 9-beam IMRT plans (CLINICAL), and to du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t combined library, including the modeled shapes, would increase the workload of the physicist at the planning (2h per plan optimization). However, the need for adaptive strategies, based on the generation of multiple treatment plans, is largely accepted and some clinical tools, such as automatic planning tools [41], may ease their clinical implementation. Two ongoing clinical trials based on the use of the planning library showed that 3 to 15 min is required to select the plan-of-the-day at each treatment fraction [10,42].…”
Section: Ctv: Clinical Target Volumementioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t combined library, including the modeled shapes, would increase the workload of the physicist at the planning (2h per plan optimization). However, the need for adaptive strategies, based on the generation of multiple treatment plans, is largely accepted and some clinical tools, such as automatic planning tools [41], may ease their clinical implementation. Two ongoing clinical trials based on the use of the planning library showed that 3 to 15 min is required to select the plan-of-the-day at each treatment fraction [10,42].…”
Section: Ctv: Clinical Target Volumementioning
confidence: 99%
“…In this work, we have developed the first system for automatic generation of deliverable plans for non-coplanar robotic treatment (autoROBOT). Basis of the autoROBOT planning system is a multi-criterial optimizer that was also the core of a recently developed system for automatic VMAT plan generation for C-arm linacs [19,27]. The developed autoROBOT planning system was first evaluated by comparing manually generated prostate SBRT plans with autoROBOT plans.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches have been recently developed for delivery systems whose optimization algorithms do not allow adaptive online replanning procedures. The most common strategy consist of creating offline treatment plans libraries in which different possible scenarios are collected (e.g., different filling of hollow organs at risk), allowing the user to choose online the plan that fits the best with the anatomy of the day …”
Section: Discussionmentioning
confidence: 99%